The Coupling Dynamic Analysis and Field Test of TBM Main System under Multipoint Impact Excitation - Junzhou Huo; Hanyang Wu; Guangqing Li; Wei Sun; Jing Chen (Shock and Vibration)
Damage by excessive vibration is serious engineering problem in TBM boring process. Dynamic characteristic analysis is essential for TBM antivibration design. According to TBM horizontal support structure, a dynamic coupling nonlinear model is established, with consideration of time-varying impact load and multicomponent complex relationship from cutter to gripper shoe. A set of field vibration tests is set up to accurately collect data under extreme work conditions; then, field data is collected from Liaoning northwest engineering. Field data is applied to validate simulation model to make sure time-varying damping stiffness, support cylinder stiffness, and the TBM machine stiffness distribution are reasonable. Simulation indicates the weakest part of TBM in axial and torsional DOF is the cylinder hinge and the connection shaft between motor and pinion, and the horizontal and vertical weak parts are bull gear. It also shows that, in normal excavation conditions, the acceleration amplitude of the cutterhead in three directions ranges from 1.5 g to 2 g. These results provide theoretical basis for the antivibration design and structural optimization of TBM.